2017
DOI: 10.1177/1077801217697266
|View full text |Cite
|
Sign up to set email alerts
|

A Template Analysis of Intimate Partner Violence Survivors’ Experiences of Animal Maltreatment: Implications for Safety Planning and Intervention

Abstract: This study explores the intersection of intimate partner violence (IPV) and animal cruelty in an ethnically diverse sample of 103 pet-owning IPV survivors recruited from community-based domestic violence programs. Template analysis revealed five themes: (a) Animal Maltreatment by Partner as a Tactic of Coercive Power and Control, (b) Animal Maltreatment by Partner as Discipline or Punishment of Pet, (c) Animal Maltreatment by Children, (d) Emotional and Psychological Impact of Animal Maltreatment Exposure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 49 publications
2
44
0
1
Order By: Relevance
“…Findings from recent qualitative studies (e.g., Collins et al 2017;McDonald et al 2015McDonald et al , 2017 suggest that the type of maltreatment that children are exposed to, the motivations they attribute to the violence, and their emotional and behavioral reactions to AM, may have important implications for understanding the link between AM exposure and children's socioemotional adjustment within the context of violent families. In particular, recent studies of pet-owning women and children recruited from community-based IPV services reported that children are often directly exposed to AM perpetrated by a caregiver/ parent that is aimed to: (a) coerce and force the compliance of an intimate partner (McDonald et al 2015(McDonald et al , 2017, (b) punish the pet for misbehavior (McDonald et al 2015(McDonald et al , 2017, and/or (c) coerce or punish the child (McDonald et al 2017).…”
Section: Animal Maltreatment Exposure Ipv and Child Wellbeingmentioning
confidence: 99%
“…Findings from recent qualitative studies (e.g., Collins et al 2017;McDonald et al 2015McDonald et al , 2017 suggest that the type of maltreatment that children are exposed to, the motivations they attribute to the violence, and their emotional and behavioral reactions to AM, may have important implications for understanding the link between AM exposure and children's socioemotional adjustment within the context of violent families. In particular, recent studies of pet-owning women and children recruited from community-based IPV services reported that children are often directly exposed to AM perpetrated by a caregiver/ parent that is aimed to: (a) coerce and force the compliance of an intimate partner (McDonald et al 2015(McDonald et al , 2017, (b) punish the pet for misbehavior (McDonald et al 2015(McDonald et al , 2017, and/or (c) coerce or punish the child (McDonald et al 2017).…”
Section: Animal Maltreatment Exposure Ipv and Child Wellbeingmentioning
confidence: 99%
“…Although studies into animal cruelty have increased over the years, a drawback is that the majority of studies have focused on intentional animal cruelty and on clinical or special populations, adult populations, relying heavily on retrospective reports of childhood animal cruelty (e.g., Parfitt & Alleyne, 2016). Studies have focused on the links between cruelty and violence (e.g., Collins et al, 2018;Monsalve, Ferreira & Garcia, 2017), and associations between cruelty and behavioural problems (e.g., Baglivio et al, 2017), and links with adverse childhood experiences (Browne, Hensley & McGuffee, 2017). Most studies have not directly focused on childhood cruelty towards animals (e.g., Levitt, Hoffer & Loper, 2016;Newberry, 2017aNewberry, , 2017bSanders & Henry, 2017;Walters, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The AARAT could also prove valuable to professionals who provide support for IPV survivors struggling to decide whether to stay with or leave an abuser (Collins et al, ; Hageman et al, ). Risk assessment for future AA could be critical information for programs providing shelter for the pets of IPV survivors (Ascione, ).…”
Section: Developments In the Forensic Assessment Of Aamentioning
confidence: 99%